ISOLATION IDENTIFICATION AND CONTROL OF EARLY BLIGHT OF POTATO - KUMARI ANUPAM (International Journal of Multidisciplinary Research and Studies, 2020)
Estimates that were correct as of July 2019 suggest that the overall number of people living on our planet is somewhere in the neighborhood of 7.7 billion (Worldometer, n.d.), and that number is fast increasing with each passing second. In terms of demographic data, India is currently the second most powerful nation in the world, and the great majority of people who live in the city consider the countryside to be their permanent residence. Every living creature is required to have a meal in the morning and another in the evening on a regular basis. Breakfast and dinner are the most important meals. As a consequence of this, the vast majority of people all over the globe depend on the staple food crops, such as rice, wheat, and maize, in order to meet their day-to-day needs for the intake of food and to prevent themselves from going hungry. (Hong et al., 2017 and Spooner, 2013) Potatoes, scientifically known as Solanum tuberosum and colloquially referred to as spuds, are the crop that are ranked as the world's fourth most significant and important staple food crop, after cereals. The word "staple" refers to a category of food that is included in the diets of the vast majority of individuals within a certain community. According to the Resource library that is kept up to date by National Geographic (n.d.), the foods that are considered to be "staples" are those that are eaten often and on a daily basis. When growing any sort of crop, having soil that is not only nutrient-dense but also in healthy shape is of the utmost significance.